Розробка додатку для автоматизації оцінки рівня якості флексодруку - Чеботарьов, Р. І. (ХНУРЕ, 2024)
The work describes the developed application for the automated calculation of the complex quality indicator and assessment of the quality level of plastic tubes, its architecture and functionality. This application can be used in production to automate the quality control process and provide reports on the current level of defects. The development of this software will allow to automate the quality management process in production, speed up and improve the quality assessment process.
Keywords: якість флексодруку; флексодрук